How to get postural stability in taekwondo - Kinoshita, M.; Fujii, N. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to evaluate techniques for keeping postural stability in Taekwondo continuous fast kicks. The results were summarized as follows: i) GOOD subjects can control their movement so as to offset the angular momentum of the whole body around the horizontal axis, ii) Good subjects produce smaller angular momentum around the vertical axis to maintain stability, and iii) POOR subjects try to offset the larger angular momentum produced by larger kicking leg motion, iv) Larger kicking motion makes athlete look like POOR. Taken together, our data suggest that coaches should be aware that athletes have to limit these to utilize the knee and hip joints motion of kicking leg and support leg motion to get kicking height and driving force. These motions are also the reason why POOR subjects cannot maintain stability in continuous fast kicks.